VLNDEF (Victoria Land Network for DEFormation control). Monumentation during the GANOVEX VIII – ITALIANTARTIDE XV: Survey and Data Processing - Mancini, F; Capra, A; Gandolfi, S; Sarti, P; Vittuari, Luca (Editore Università di Siena. Dipartimento di Scienze della Terra Luogo pubbl. Siena, 2004)
In the frame of the 1999-2000 Italian expedition in Antarctica a scientific programme for geodynamic purposes in the northern Victoria Land begun. The new project VLNDEF (Victoria Land Network for DEFormation control) deals with the monitoring of crustal deformations within the investigated area. The newly-monumented GPS stations and the following field geodetic surveys (hereafter discussed) extended an existing GPS geodetic network located close to the area of Terra Nova Bay where a GPS Permanent Station is also available. At the end of XV Italian expedition the network covered an area included between the latitude of 71 and 74.5 degrees South and longitude ranging between 160 and 170 degrees East (Capra et al., 2000). Later on, in the frame of the 2000-2001 expedition, the network was extended as far as latitude of 76 degrees South, with the monumentation of the southernmost points. Activities and results of the latter are not reported in this paper. The extension of the monumented network needed of operations carried out both from the research vessel Polar Duke employed by the expedition (points located at north of the 72th south parallel) and from the Italian Mario Zucchelli Station at Terra Nova Bay (all the remaining southern points). This paper deals with the field operations and survey carried out within the joint German-Italian Antarctic expedition 1999-2000 (Mancini, 2001). Results, accuracies, problem related to the reference frame and possibility to detect deformations by further investigation will be discussed. VLNDEF is a project within the activities of GIANT (Geodetic Infrastructure of ANTarctica) SCAR (Scientific Committee on Antarctic Research) programme and is supervised by the SCAR group of specialists of ANTEC (Antarctic NeoTECtonics). In the frame of the 1999-2000 Italian expedition in Antarctica a scientific programme for geodynamic purposes in the northern Victoria Land begun. The new project VLNDEF (Victoria Land Network for DEFormation control) deals with the monitoring of crustal ...